The new confessions of an economic hit man - Perkins, John 1945- (Berrett-Koehler Publishers, Inc., 2016)
"Featuring 12 explosive new chapters, this new edition of the New York Times bestseller brings the story of Economic Hit Men up-to-date and, chillingly, home to the U. S....but it also gives us hope and the tools to fight back"...Provided by publisher
Includes bibliographical references (page 343-353) and index
Keywords: Perkins, John -- 1945-; United States -- National Security Agency -- Biography; Chas. T. Main, Inc; World Bank -- Developing countries; Geschichte 1900-2000; Geschichte 1971-1991; Geschichte 1963-2001; Entwicklungsländer; Geschichte; Intelligence officers -- United States -- Biography; Economists -- United States -- Biography; Energy consultants -- United States -- Biography; Corporations, American -- Corrupt practices; Imperialism -- History -- 20th century; Imperialism -- History -- 21st century; Wirtschaftskriminalität; Wirtschaftsimperialismus; USA; Biografie